Enhancing Students’ Self-Confidence and Critical Thinking Ability in Identifying Physical and Chemical Changes Using Technology-Assisted Constructivist Approaches - Ajayi, Victor Oluwatosin; Ameh, Rachael Folake; Alabi, Ayodeji Olorunmeye (Journal of Research in Science and Mathematics Education, 2025)
Purpose: This study examined the effectiveness of technology-assisted constructivist approaches—namely, the Predict-Explain-Observe-Explain (PEOE) and Invitation-Exploration-Proposing Explanation-Taking Action (IEPT) models—in enhancing senior secondary students’ self-confidence and critical thinking in identifying physical and chemical changes. Methodology: A quasi-experimental, non-randomized pre-test, post-test control group design was employed. Instruments used were the Physical and Chemical Changes Self-Confidence Scale (PCCSS) and the Critical Thinking Ability Test (CTAT), both validated by subject experts. The study population consisted of 5,543 SS1 Chemistry students in Dekina Local Government Area, Kogi State, Nigeria. A sample of 228 students from six schools was selected through multi-stage sampling. Four research questions and four null hypotheses guided the study. Data were analyzed using mean, standard deviation, and Analysis of Covariance (ANCOVA). Findings: Results indicated statistically significant differences in students’ mean self-confidence and critical thinking scores across the PEOE, IEPT, and traditional discussion groups [F(2, 227) = 2325.074, p < .05; F(2, 227) = 209.004, p < .05]. However, no significant interaction effects were found between instructional method and gender on students’ self-confidence or critical thinking scores [F(2, 227) = .085, p > .05; F(2, 227) = .225, p > .05]. Significance: The study concludes that technology-assisted constructivist strategies significantly improve students’ cognitive and affective engagement in Chemistry. It is recommended that Chemistry educators integrate the PEOE and IEPT models to foster deeper understanding, self-confidence, and critical thinking in distinguishing between physical and chemical changes.